Nutrition-relevant policy in West Africa: A comprehensive review - Casu, Laura; Diatta, Ampa Dogui; Uzhova, Irina; Dramé, Mariame; Kaboré, Judith; Touré, Fanta; Becquey, Elodie; Verstraeten, Roosmarijn (International Food Policy Research Institute, 2022)
Malnutrition continues to be a major health burden in low- and middle-income countries (LMICs) and is one of the predominant risk factors for ill health and death, with women and children being most vulnerable. Most countries in the region show variable, little, or no progress in meeting most of the global nutrition goals (Development Initiatives 2020); therefore, stunting and wasting among children under five (U5s), low birth weight, anemia among women of reproductive age (WRA), and the epidemic of overweight/obesity remain priorities for West African policymakers. None of the countries in the region are on track to meet the targets for low birth weight (LBW), anemia among WRA (Development Initiatives 2020), or overweight/obesity; and nutrition-related noncommunicable diseases (NR-NCDs) are on the rise (Verstraeten and Diop 2018; Development Initiatives 2020; Popkin, Corvalan, Grummer-Strawn 2020). With the COVID-19 pandemic aggravating the pre-existing malnutrition burden (Osendarp et al. 2021), and the 2030 deadline for reaching the Sustainable Development Goals (SDGs) fast approaching, it is a critical time for action. The region’s unequal and limited progress has been attributed to, among other things, political instability and lack of resources (Development Initiatives 2020). Suggestions for ways to achieve SDG Target 17.14 (Enhance policy coherence for sustainable development) have included better implementation of policies and actions in response to specific identified needs and priorities; a further suggested approach is increased coherence and coordination across nutrition-relevant sectors (Pelletier et al. 2012; Gillespie et al. 2013; Hawkes 2016). Policy coherence analysis also promises to be an important tool for improving the efficiency and effectiveness of food policy and practice (Parsons and Hawkes 2019).